Trade Unions in the European Union - Jeremy Waddington; Torsten Müller; Kurt Vandaele (Peter Lang International Academic Publishers, 2023)
Trade unions have repeatedly been challenged by neoliberal programmes implemented within Member States of the European Union (EU) and at the European level. The twentyseven country chapters at the core of this book chart the features of the neoliberal challenge in the EU Member States and the measures implemented by unions in their attempts to adapt to changed circumstances since 2000. It is clear that union activity, either independently or in conjunction with allies, will be at the centre of revitalization campaigns if the pieces left from the neoliberal challenges are to be picked up and wielded into a coherent response. This book offers a comprehensive comparative overview of the development, structure, and policies of national trade union movements in the EU. It presents an in-depth analysis of the challenges facing these organizations and their strategic and policy responses from 2000 to 2020.
Keywords: 320; European; Jeremy; Kurt; Müller; Torsten; Trade; Union; Unions; Vandaele; Waddington